The Implication of Serum Autoantibodies in Prognosis of Canine Mammary Tumors - Yuan, Stephen Hsien-Chi; Chang, Shih-Chieh; Chou, Pei-Yi; Yang, Youngsen; Liu, Hao-Ping (Animals (Basel), 2022)
Canine mammary tumor (CMT) is the most prevalent neoplasm in female dogs. Tumor recurrence and metastasis occur in malignant CMT (MMT) dogs after surgery. Identification of serum prognostic biomarkers holds the potential to facilitate prediction of disease outcomes. We have identified CMT-associated autoantibodies against thymidylate synthetase (TYMS), insulin-like growth factor-binding protein 5 (IGFBP5), hyaluronan and proteoglycan link protein 1 (HAPLN1), and anterior gradient 2 (AGR2), i.e., TYMS-AAb, IGFBP5-AAb, HAPLN1-AAb, and AGR2-AAb, respectively, by conducting serological enzyme-linked immunosorbent assays (ELISA). Herein we assessed serum AAb levels in 11 MMT dogs before and after surgery, demonstrating that IGFBP5-AAb and HAPLN1-AAb significantly decrease at 3- and 12-months post-surgery (p < 0.05). We evaluated the correlation between the presurgical AAb level and overall survival (OS) of 90 CMT dogs after surgery. Kaplan-Meier survival analysis reveals that IGFBP5-AAbHIgh and TYMS-AAbHigh are significantly correlated with worse OS (p = 0.017 and p = 0.029, respectively), while AGR2-AAbLow is correlated with somewhat poorer OS (p = 0.086). Areas under a time-dependent receiver operating characteristic curve (AUC) of IGFBP5-AAb and TYMS-AAb in predicting OS of MMT dogs are 0.611 and 0.616, respectively. Notably, MMT dogs presenting TYMS-AAbHigh/IGFBP5-AAbHigh/AGR2-AAbLow have worst OS (p = 0.0004). This study reveals an association between the serum AAb level and CMT prognosis.